What Do Competitiveness Rankings Show Us? Substantiation and Informativeness of the World Economic Forum’s Competitiveness Ranking - Vargha, Bálint Tamás; Németh, Erzsébet; Pályi, Katalin Ágnes (Public Finance Quarterly, 2019)
In the past few years, competitiveness has become one of the main focus of economic policy. This study provides an overview of the measurement risks mentioned in the references in connection with the measuring of competitiveness, and using the method of document analysis it evaluates whether the competitiveness index of the World Economic Forum meets the requirements of science and whether it provides adequate information for decision-makers and the professional public. The paper establishes that international competitiveness measurements sum up several relevant data sources that provide valuable information about national economies and socio-economic development levels. However, the large quantities of data of a quite diverse nature do not allow such rankings to inform about a nation’s competitiveness in a scientific depth. Choice of some data sources of the World Economic Forum’s Global Competitiveness Report was not based on their connection with competitiveness, and in some cases are inconsistent.